The Physical Activity-BMI Paradox: Unraveling Gender Disparities and Nutritional Status Complexities in SMK Muhammadiyah 2 Tangerang - Rizni Fitriana; Chairinda Dachwan; Zahra Nurusshofa; Yogia Ikhsas; Rafiqa Husna Amalia; Khusnul Khotimah (Jurnal Promosi Kesehatan Indonesia, 2026)
Background: Urban adolescents in Indonesia face the dual challenges of epidemiological transition and the double burden of malnutrition. Although physical activity is a key determinant of health, the association with Body Mass Index (BMI) and nutritional status among vocational high school (SMK) students remains insufficiently explored, particularly using validated assessment tools. Therefore, this study aimed to examine the relationship between physical activity, BMI, and nutritional status.Methods: A cross-sectional study was conducted among 102 tenth-grade students (54 females, 48 males) aged 14–16 years at SMK Muhammadiyah 2 Tangerang. Respondents were recruited through convenience sampling, and physical activity was assessed using the validated Physical Activity Questionnaire for Adolescents (PAQ-A), categorized into three levels. BMI was calculated from standardized anthropometric measurements. In addition, data were analyzed using Chi-square tests, One-Way ANOVA, and Spearman correlation (α=0.05).Results: The results showed that approximately 83.3% of adolescents were insufficiently active. A significant gender gap was identified, with males remarkably more inclined to be active (70.6% of the active group, p=0.004). Contrary to conventional expectations, no significant association was found between physical activity levels and BMI (p=0.631) or categorical nutritional status (p=0.279). The highest prevalence of normal nutritional status was paradoxically observed in the moderately active, not the most active, group (72.7%). It indicates the need for a paradigm shift in adolescent health promotion from a weight-centric physical activity agenda to gender-sensitive, holistic interventions aimed at overall well-being, recognizing that the benefits may not be directly visible in short-term anthropometric measures.Keywords: Physical activity, Adolescent health, Body mass index, Nutritional status, Gender disparity